Immune thrombocytopenia (ITP) World Impact Survey (iWISh): Patient and physician perceptions of diagnosis, signs and symptoms, and treatment. Issue 2 (19th December 2020) - Cooper, Nichola; Kruse, Alexandra; Kruse, Caroline; Watson, Shirley; Morgan, Mervyn; Provan, Drew; Ghanima, Waleed; Arnold, Donald M.; Tomiyama, Yoshiaki; Santoro, Cristina; Michel, Marc; Laborde, Serge; et al.
Abstract: Immune thrombocytopenia (ITP) is now well‐known to reduce patients' health‐related quality of life. However, data describing which signs and symptoms patients and physicians perceive as having the greatest impact are limited, as is understanding the full effects of ITP treatments. I‐WISh (ITP World Impact Survey) was an exploratory, cross‐sectional survey designed to establish the multifaceted impact of ITP, and its treatments, on patients' lives. It focused on perceptions of 1507 patients and 472 physicians from 13 countries regarding diagnostic pathway, frequency and severity of signs and symptoms, and treatment use. Twenty‐two percent of patients experienced delayed diagnosis (caused by several factors), 73% of whom felt anxious as a result. Patients rated fatigue among the most frequent, severe symptom associated with ITP at diagnosis (58% most frequent; 73% most severe), although physicians assigned it lower priority (30%). Fatigue was one of the few symptoms persisting at survey completion (50% and 65%, respectively) and was the top symptom patients wanted resolved (46%). Participating physicians were experienced at treating ITP, thereby recognizing the need to limit corticosteroid use to newly‐diagnosed or first‐relapse patients and espoused increased use of thrombopoietin receptor agonists and anti‐CD20 after relapse in patients with persistent/chronic disease. Patient and physicians were largely aligned on diagnosis, symptoms, and treatment use. I‐WISh demonstrated that patients and physicians largely align on overall ITP symptom burden, with certain differences, for example, fatigue. Understanding the emotional and clinical toll of ITP on the patient will facilitate shared decision‐management, setting and establishment of treatment goals and disease stage‐appropriate treatment selection.